Molecular cloning and analysis of recombinant major antigens of Ehrlichia risticii. - Dutta, S K (1991)
The genome of Ehrlichia risticii, the etiologic agent of Potomac horse fever, was cloned in the lambda gt11 expression vector. The efficiency of recombinant phage production with different restriction fragments of E. risticii DNA was generally between 20 and 95%. The antigen-positive frequency, detected by immunoscreening with E. risticii antibodies, was between 8 and 40 per 10(4) recombinants. Four (70, 55, 51, and 44 kDa) major antigens of E. risticii were identified from the recombinant phages by using recombinant antigen-selected monospecific antibodies. Characterization of three (70, 55, and 44 kDa) of these recombinant antigens indicated that the 70- and 44-kDa polypeptides were beta-galactosidase fusion products that were dependent on isopropylthiogalactoside induction for expression; they contained about 50 and 73%, respectively, of the native polypeptides. The 55-kDa antigen was a nonfusion protein expressed independently of isopropylthiogalactoside induction; it was a complete protein with a molecular weight identical to that of its native counterpart. The cloned E. risticii DNAs from of the recombinants expressing 70-, 55-, and 44-kDa proteins were 3.5, 3.9, and 4.8 kb, respectively, in size, and they were unique. The insert DNAs hybridized to multiple restriction fragments of the genomic DNA, the sum of the sizes of which was much greater than that of the corresponding insert. Mice immunized with the affinity-purified 55-kDa recombinant antigen produced a high titer of antibody in serum as measured by an enzyme-linked immunosorbent assay and gave a monospecific reaction by Western immunoblotting. Challenge infection of these immunized mice showed low protection from clinical infection.